Child temperament and child-teacher relationship quality: Implications for children’s emotional functioning during preschool period - Susa-Erdogan, Georgiana; Benga, Oana; Albu-Răduleț, Mihaela; Macovei, Teodora (Frontiers in Psychology, 2022)
Although, in the last years several studies have moved beyond analyzing the role of mother-child relationship in the association between child temperament and child emotional functioning, our knowledge is still limited about which fine-grained temperamental components of child reactivity and self-regulation are associated with child-teacher relationship quality. Also, fewer studies have looked at the moderating role of child-teacher relationship in the association between child temperament and child internalizing/externalizing problems during early childhood. The present study examined the relation between components of child temperamental Negative Affectivity, Surgency, and Effortful Control and child-teacher relationship quality (i.e., closeness, conflict) in preschool children. In addition, our aim was to test the moderating effect of the child-teacher relationship on the association between temperament and internalizing and externalizing problems. One hundred Romanian preschoolers (55 boys, mean age = 4.04 years) participated in this study. Mothers assessed their child’s temperament by completing the Children’s Behavior Questionnaire (Rothbart et al., 2001) and externalizing and internalizing problems with the Child Behavior Checklist (Achenbach & Rescorla, 2001). Child-teacher relationship quality was evaluated by children’s teachers using the Student-Teacher Relationship Scale (Pianta, 2001). Our results revealed that teachers rated their relationship as less conflictual with children who were assessed by their mothers as better in shifting and focusing attention, enjoying situations involving low stimulus intensity and displaying higher levels of Shyness, Sadness and Activity Level. Moreover, higher levels of Discomfort were associated with more conflict and less closeness while emotional reactivity such as Sadness, Fearfulness, and Activity Level were positively associated with closeness. Teacher-child closeness was associated with three temperamental self-regulation factors in the expected direction, except inhibitory control. Furthermore, results revealed a statistically significant interaction between child temperamental Shyness and child-teacher closeness in the prediction of child internalizing problems. Thus, when child-teacher closeness was low, there was a significant and positive relationship between child temperamental Shyness and child internalizing problems. Results highlight the importance of child-teacher relationship quality in relation to child temperament and social–emotional development during preschool period.